Validation of a Method for Quantification of Lutein in Spinach Using High-Performance Liquid Chromatography: Interlaboratory Study. (19th April 2020) - Sonoda, Takefumi; Hiejima, *Yusuke; Koiwa, Tomohiro; Asano, Masahiro; Kotake, Eiichi; Yasui, Akemi; ,
Abstract: Background: Lutein is gaining attention as a strong antioxidant contained in foods. It accumulates in the human blood and retina, and is considered to play an important role in the body, especially in the eyes. Objective: A method to determine the lutein content of raw spinach ( Spinacia oleracea L.) was developed with the aim of its enactment as a Japanese agricultural standard (JAS) measurement method for components beneficial to human health. Methods: An interlaboratory study was conducted to evaluate an analytical method for the determination of lutein in spinach. The detection limit and quantification limit of lutein for this method were 0.2 and 0.7 mg/kg, respectively. Twelve participating laboratories independently analyzed test samples (five pairs of blind duplicates) using high-performance liquid chromatography (HPLC). Results: After removal of a few outliers, the repeatability relative standard deviation (RSDr ), reproducibility (RSDR ), and predicted RSDR of the evaluated method were 3.4–7.5, 4.6–13, and 7.5–8.5%, respectively, in a concentration range from 64.9–150 mg/kg. Conclusions: The HorRat values (RSDR /predicted RSDR ) of the lutein concentration were calculated to be 0.61–1.6. Highlights: The study results indicate the acceptable precision of this method.